Measurement of Leakage Current in Wet and Polluted Conditions Using Different Sensing Electrodes - Šárpataky Ľuboš; Dolník Bystrík (Acta Electrotechnica et Informatica, 2022)
Insulators, as the main insulating element of transmission lines, are exposed to various stresses, which affect the operation and thus the reliability of electricity supply. To improve the reliability of insulators, it is necessary to monitor their condition. Thanks to the development of computer technology, it is possible to process a large amount of data, which popularizes the possibility of diagnostics online. Factors that affect reliability, failure rate, and losses the most, are pollution and humidity. Our research is focused on monitoring and evaluating the applicability of various sensing electrodes for measuring leakage current on glass insulators. Relative humidity and pollution levels changes can give us a clear view of the used measuring method and how different sensing electrodes can affect the value of leakage current.